Release film, method for producing the same, and laminate
The release film, featuring a release layer with specific analytical and physical characteristics on a polyester resin base layer, addresses the peeling and heating-related issues of non-silicone release films by ensuring excellent coating and controlled release properties.
Patent Information
- Application Number
- JP2024028296
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-21
- Filing Date
- 2024-02-28
- Publication Date
- 2025-04-03
AI Technical Summary
Non-silicone release films used in the production of surface protection films tend to have heavy peeling issues with coated layers and exhibit increased release force upon heating, making them difficult to peel off even after heating.
A release film with specific physical properties, including a release layer on a polyester resin base layer, analyzed by time-of-flight secondary ion mass spectrometry to ensure low dimethylsiloxane content, low surface free energy, controlled polarity and hydrogen bonding forces, and optimized peeling forces before and after heating.
The release film achieves excellent coating properties and controlled release forces, allowing for easy peeling of mating members with a light force both before and after heating, thereby addressing the drawbacks of non-silicone release films.
Smart Images

Figure 2025048703000001 
Figure 2025048703000002 
Figure 2025048703000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a release film, a method for producing the same, and a laminate. [Background technology]
[0002] A laminated film with excellent releasability is a member that can be peeled off at the interface with an adjacent mating member, and is used as a protective film for the adhesive layer in adhesive products and a carrier film in the processing of various industrial products. Particularly in recent years, the demand for laminated films with excellent releasability has been increasing from the viewpoint of increasing the manufacturing speed and improving the quality of various products.
[0003] As a laminated film with excellent releasability, a film containing a silicone compound in the release layer (hereinafter referred to as a silicone release film) is most commonly used from the viewpoints of industrial productivity and heat resistance (for example, Patent Document 1). However, since the silicone release film contains a silicone compound in the release layer, the surface free energy of the release layer is low, and therefore the coating property of the counterpart member becomes poor due to repelling of the paint for forming the counterpart member and entrapment of air bubbles, etc., and the counterpart member may not be formed uniformly.
[0004] On the other hand, for example, in the case of optical components and electronic components that require high precision, a surface protection film having an adhesive layer is attached to a laminated film substrate in order to prevent the surface from being scratched during processing, assembly, inspection, transportation, etc. (Patent Document 2) Silicone release films have traditionally been used as release films used in the manufacture of such surface protection films (Patent Document 3), but in recent years, it has been known that release films that do not contain silicone compounds (hereinafter referred to as non-silicone release films) can be suitably used to prevent the surface of the component to which the surface protection film is attached from being contaminated with silicone compounds (Patent Document 4).
[0005] In response to these issues, studies have been conducted on the use of long-chain alkyl group-containing resins, olefin resins, fluorine compounds, and wax-based compounds, particularly long-chain alkyl group-containing resins, as the main material for non-silicone release films (for example, Patent Documents 5 to 7). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2010-155459 A [Patent Document 2] JP 2016-017109 A [Patent Document 3] JP 2012-224811 A [Patent Document 4] JP 2019-194337 A [Patent Document 5] JP 2004-351626 A [Patent Document 6] JP 2004-230772 A [Patent Document 7] JP 2015-199329 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, when the non-silicone release films described in Patent Documents 5 to 7 are used for the manufacture of surface protective films, etc., the layer (e.g., adhesive layer, etc.) provided on the release film by coating or the like tends to peel off more heavily than when a silicone release film is used. In addition, non-silicone release films generally have the problem that the peeling force of the layer provided on the release film by coating or the like increases significantly when heated. For example, when the present inventors verified the film described in Patent Document 5, it was found that when an adhesive tape was attached to the resin layer and peeled off after heating, the adhesive tape peeled off significantly more heavily. In addition, when a long-chain alkyl group-containing resin and a crosslinking agent are used in combination as in the film described in Patent Document 6, or when a long-chain alkyl acrylate resin and a melamine resin are used in combination as in the film described in Patent Document 7, the change in peeling force of the adhesive tape due to heating is small, but the peeling force of the adhesive tape is still high, and it was found that peeling is difficult even after heating.
[0008] Therefore, an object of the present invention is to provide a release film which overcomes the above-mentioned drawbacks, has excellent coatability for a coating composition which forms a layer formed by coating or the like, allows the mating member to be peeled off with a light force, and allows the mating member to be peeled off with a light force even after heating. [Means for solving the problem]
[0009] As a result of intensive research in view of the above problems, the present inventors have found that by using a release film having specific physical properties, a release film for producing a surface protective film having excellent coatability, releasability, and controllability of peeling force by heating can be obtained, and have completed the present invention. The present invention has the following configuration. That is, [I] A release film having a release layer on at least one side of a polyester resin substrate layer, wherein when the surface of the release layer is analyzed by time-of-flight secondary ion mass spectrometry, where K is the peak intensity of a positive ion fragment detected at maximum intensity and P is the peak intensity of a positive ion fragment derived from dimethylsiloxane, P / K is less than 0.01, the surface free energy of the release layer is 25.0 mN / m or less, and the ratio γh / γp of polar force γp to hydrogen bonding force γh in the release layer is 1.0 or less. [II] A release film having a release layer on at least one side of a polyester resin substrate layer, wherein when the surface of the release layer is analyzed by time-of-flight secondary ion mass spectrometry, where K is the peak intensity of a positive ion fragment detected at the maximum intensity and P is the peak intensity of a positive ion fragment derived from dimethylsiloxane, P / K is less than 0.01, and the release layer has a receding contact angle of water, θr, of 85° or more. [III] The release film according to [I], wherein the release layer has a receding contact angle θr of water of 85° or more. [IV] The release film according to any one of [I] to [III], wherein R1 is an initial tape peel strength of the release layer, and R2 is a tape peel strength of the release layer after heating at 50°C for 1 hour, and R1 is 4.0 N / 50 mm or less, and R2 / R1 is 5.0 or less. [V] The release film according to any one of [I] to [IV], which contains at least one of a biomass raw material and a recycled raw material. [VI] The release film according to any one of [I] to [V], wherein the release layer contains a polyester resin having at least one of an SSIA group and a COOH group. [VII] The release film according to any one of [I] to [VI], wherein, when the surface of the release layer is analyzed by time-of-flight secondary ion mass spectrometry, F / K is less than 0.001, where F is the peak intensity of a positive ion fragment derived from methylolmelamine. [VIII] A laminate comprising a pressure-sensitive adhesive layer on the release layer side of the release film according to any one of [I] to [VII]. [IX] A method for producing a release film according to any one of [I] to [VII], comprising the steps of: a coating step of coating at least one surface of a polyester resin substrate sheet with a resin composition for forming a release layer; a stretching step of stretching the polyester resin substrate sheet after the resin composition has been coated in at least one axial direction; and a heat treatment step of heating the polyester resin substrate sheet after the stretching to 150°C or higher to form a release layer, in this order. Effect of the Invention
[0010] According to the present invention, it is possible to provide a release film which has excellent coatability for a coating composition that forms a layer provided by coating or the like, which allows the mating member to be peeled off with a light force, and which allows the mating member to be peeled off with a light force even after heating. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The release film of the present invention will be described in detail below. One embodiment of the present invention is a release film having a release layer on at least one side of a polyester resin substrate layer, and when the surface of the release layer is analyzed by time-of-flight secondary ion mass spectrometry, the peak intensity of the fragment of a positive ion detected at the maximum intensity is K, and the peak intensity of the fragment of a positive ion derived from dimethylsiloxane is P, where P / K is less than 0.01, the surface free energy of the release layer is 25.0 mN / m or less, and the ratio γh / γp of the polar force γp to the hydrogen bonding force γh in the release layer is 1.0 or less.
[0012] First, the meaning of these physical properties in the release film of the present invention and examples of control methods will be described. The release film of the present invention has a release layer on at least one side of a polyester resin substrate layer from the viewpoint of reducing deterioration in quality of a member to be bonded to the surface (hereinafter, sometimes referred to as a counterpart member), and when the surface of the release layer is analyzed by secondary ion mass spectrometry, the peak intensity of the fragment of the positive ion detected at the maximum intensity is K, and the peak intensity of the fragment of the positive ion derived from dimethylsiloxane is P, where P / K is less than 0.01.
[0013] P / K can be calculated from the peak obtained by time-of-flight secondary ion mass spectrometry, and the method of time-of-flight secondary ion mass spectrometry will be described in detail later. The fact that the release layer satisfies the above characteristics means that the release layer contains few components derived from silicone compounds (e.g., dimethylsiloxane, etc.). This characteristic contributes to reducing the deterioration of the quality of the mating member when used as a release film, for example. More specifically, if the mating member to be bonded to the release layer is an optical member or an electronic member, the migration of the silicone compound to the mating member is suppressed, and problems such as poor electrical conductivity, poor insulation, and pinhole defects can be reduced. In other words, by reducing the components derived from dimethylsiloxane in the release layer, the release layer can be made to reduce the contamination of the mating member surface caused by the silicone compound.
[0014] From the above viewpoint, P / K is less than 0.01, and less than 0.001 is more preferable when the release film is used for optical components or electronic components that may malfunction due to a small amount of silicone compound. From the above viewpoint, the smaller P / K is preferable, and the lower limit is 0. There is no particular limitation on the method for making P / K less than 0.01, but a representative method is a method for adjusting the composition and film thickness of the release layer described later. More specifically, as an example of the composition, a method for not using (or reducing the amount of) a silicone compound in the release layer, and for containing a long-chain alkyl resin, an olefin resin, a fluorine compound, a wax compound, or the like, preferably a long-chain alkyl resin, can be mentioned. More specifically, as a method for adjusting the film thickness, a method for adjusting the concentration of the solid content contained in the resin composition for forming the release layer described later, and a method for adjusting the amount of coating composition applied depending on the depth of the groove of the wire bar used in the bar coating method can be mentioned.
[0015] As an embodiment of the present invention, a release film having a surface free energy of a release layer of 25.0 mN / m or less is given from the viewpoint of improving the peelability from the mating member. Satisfying the above characteristics means that the release film has excellent applicability of a coating composition forming the mating member, such as an acrylic adhesive or a silicone adhesive, and excellent releasability. The surface free energy is an index of wettability when in contact with a liquid, and is expressed as the sum of three components: dispersion force, polar force, and hydrogen bond force.
[0016] The surface free energy, dispersion force, polar force, and hydrogen bond force can be measured and calculated by the geometric mean method based on the extended Fowkes formula (extended Fowkes formula) using the contact angle of the solution, and the detailed measurement method will be described later. The higher the surface free energy of the release layer, the higher the affinity of the coating composition for forming the counterpart member and the release layer, and the coatability of the coating composition is improved. On the other hand, if the surface free energy of the release layer exceeds 25.0 mN / m, the affinity between the release layer and the coating composition becomes too large, so that the releasability of the release layer may decrease. In general, the lower the surface free energy of the release layer, the smaller the affinity between the release layer and the counterpart member, so that the counterpart member can be peeled off with a light force. On the other hand, if the surface free energy of the release layer is below 10.0 mN / m, the affinity between the release layer and the coating composition becomes too small, so that the coatability of the coating composition may decrease. From the above viewpoints, the surface free energy of the release layer of the release film of the present invention is preferably from 10.0 to 25.0 mN / m, and more preferably from 15.0 to 25.0 mN / m.
[0017] As a method for making the surface free energy of the release layer 25.0 mN / m or less, for example, a method for forming the release layer from a resin composition containing a release agent (A) described later can be mentioned. In addition, from the viewpoint of the process, it is also effective to set the heat treatment temperature after stretching in the width direction (the drying temperature of the coating composition in the case of off-coating) to the preferred range described later. These methods can be used in combination as appropriate.
[0018] As an embodiment of the present invention, from the viewpoint of ensuring releasability even after the heating process, a release film in which the ratio γh / γp of the polar force γp to the hydrogen bond force γh in the release layer is 1.0 or less can be mentioned. Satisfying the above characteristics means that the release film has excellent control of the peel force between the release layer and the mating member after heating. In general, a large polar force γp of the release layer means that the resin components forming the release layer have a high ratio of resin components having polar molecules. In addition, a large hydrogen bond force γh means that the resin components forming the release layer have a high ratio of resin components having molecules capable of forming hydrogen bonds. These γp and γh are generally used as indicators of the strength of the affinity between the release layer and the mating member, but as a result of intensive research by the present inventors, it has been found that by adjusting the γp and γh of the release layer to a specific range as in the present invention, it is easy to obtain a release film that has excellent control of the peel force between the release layer and the mating member after heating.
[0019] In order to control the surface free energy, polarity γp, and hydrogen bonding strength γh of the release layer within the above-mentioned preferred ranges, it is effective to use, for example, a release agent or material described later, particularly a random copolymer containing a long-chain alkyl group as the release agent. In addition, when the surface of the release layer is analyzed by time-of-flight secondary ion mass spectrometry, it is also effective to use a method of controlling F / K to less than 0.001, where F is the peak intensity of the fragment of a positive ion derived from methylolmelamine described later. The fact that the F / K of the release layer surface is less than 0.001 means that the release layer contains fewer components derived from melamine compounds (e.g., trimethylolmelamine, etc.). This characteristic is a characteristic that contributes to reducing the deterioration of the quality of the counterpart member when used, for example, as a release film. More specifically, if the counterpart member to be bonded to the release layer is an optical member or an electronic member, the migration of the melamine compound to the counterpart member can be suppressed, and problems such as poor conductivity, poor insulation, and pinhole defects can be reduced. That is, by reducing the components derived from methylolmelamine in the release layer, the release layer can reduce contamination of the surface of the counterpart member caused by the melamine compound. Furthermore, from the viewpoint of the process, it is also effective to form a release layer on a film uniaxially stretched in the longitudinal direction by an in-line coating method (details will be described later). These methods can also be used in combination as appropriate.
[0020] As an embodiment of the present invention, a release film having a receding contact angle θr of water of the release layer of 85° or more is exemplified from the viewpoint of improving the releasability from the counter member. Satisfying the above characteristics means that the release film has excellent releasability from the counter member represented by acrylic adhesives and silicone adhesives. Generally, the receding contact angle θr of water is used as an index showing the ease with which a liquid such as water or paint spreads on the release layer. However, as a result of intensive research by the present inventors, it has been found that by adjusting the receding contact angle θr of water of the release layer to 85° or more, preferably 90° or more as in the present invention, it is easy to obtain a release film having excellent releasability from the counter member.
[0021] In order to control the receding contact angle θr of water on the release layer within the above-mentioned preferred range, it is effective to use, for example, a release agent or material described later, particularly a random copolymer containing a long-chain alkyl group as the release agent. In addition, when the surface of the release layer is analyzed by time-of-flight secondary ion mass spectrometry, it is also effective to use a method of controlling F / K to less than 0.001, where F is the peak intensity of the fragment of a positive ion derived from methylolmelamine described later. Furthermore, in terms of process, a method of forming a release layer on a film uniaxially stretched in the longitudinal direction by an in-line coating method is also effective (details will be described later). These methods can also be used in combination as appropriate.
[0022] In the release layer of the release film of the present invention, from the viewpoint of improving the peelability from the mating member, when the initial tape peeling force is R1, it is preferable that R1 is 4.0 N / 50 mm or less. In addition, from the viewpoint of ensuring the releasability even after the heating step, when the tape peeling force of the release layer after heating at 50° C. for 1 hour is R2, it is preferable that R2 / R1 is 5.0 or less. R1 and R2 can be measured with a peel analysis device, and a specific measurement method will be described later.
[0023] By setting R1 to 4.0 N / 50 mm or less, the mating member can be peeled off with a light force at a stage before the heating step, and by setting R2 / R1 to 5.0 or less, the mating member can be peeled off with a light force even after heating. From the above viewpoints, R1 is more preferably 3.5 N / 50 mm or less, and even more preferably 3.0 N / 50 mm or less. From the above viewpoints, R2 / R1 is more preferably 4.0 or less, even more preferably 3.0 or less, and particularly preferably 1.8 or less.
[0024] The method for controlling the values of R1 and R2 / R1 is not particularly limited, but a representative method includes a method of adjusting the types and contents of the release agent (A), binder resin (B), and reactive compound (C) in the resin composition for forming the release layer described below, as described below.
[0025] The release film of the present invention has a resin layer on at least one side of a polyester resin substrate layer. The polyester resin is a general term for polymers having an ester bond as the main bond in the main chain, and specifically, those having at least one type of structural unit selected from ethylene terephthalate, propylene terephthalate, ethylene-2,6-naphthalate, butylene terephthalate, propylene-2,6-naphthalate, ethylene-α,β-bis(2-chlorophenoxy)ethane-4,4'-dicarboxylate as the main structural unit can be preferably used. Here, the main structural unit refers to a structural unit contained in a proportion of more than 50 mol% to 100 mol% or less when the total structural units constituting the resin are taken as 100 mol%.
[0026] As the polyester resin substrate layer in the release film of the present invention, it is preferable to use a polyester film from the viewpoint of heat resistance and smoothness. The polyester film refers to a sheet-like molded product containing a polyester resin as a main component, and the main component refers to a component contained in the total constituent components at more than 50 mass% and 100 mass% or less, and the same can be interpreted below. In addition, when a sheet-like molded product contains multiple types of polyester resins, if the total amount exceeds 50 mass%, the molded product can be considered to be a polyester film.
[0027] The polyester resin may contain less than 50 mol%, preferably 30 mol% or less of copolymerization units in all structural units as necessary. In addition, when heat or shrinkage stress acts on the release film, it is preferable to use a polyethylene terephthalate film or a polyethylene-2,6-naphthalate film having excellent heat resistance and rigidity as the polyester resin substrate layer. Here, the polyethylene terephthalate film refers to a film in which polyethylene terephthalate (including copolymers) accounts for more than 50 mass% and 100 mass% or less of all components constituting the film, and the same can be interpreted for a polyethylene-2,6-naphthalate film. In addition, when multiple types of resins equivalent to polyethylene terephthalate are contained due to differences in the amount of copolymerization, etc., the content of polyethylene terephthalate is calculated by adding up all the corresponding resin components. This point is also the same for a polyethylene-2,6-naphthalate film.
[0028] From the viewpoint of reducing the environmental load, the release film of the present invention preferably contains at least one of biomass raw materials and recycled raw materials, and it is more preferable that the polyester resin substrate layer contains at least one of these raw materials. Here, biomass is an organic compound derived from plants photosynthesized from carbon dioxide and water. When biomass is burned, it usually becomes carbon dioxide and water again, so that biomass can be used as a so-called carbon-neutral renewable energy. In addition, biomass raw materials refer to polyester resins containing structural units derived from biomass.
[0029] When the ratio of plant-derived carbons to the total carbons is taken as the biomass degree, for example, in an ethylene terephthalate unit, when only the ethylene glycol component is entirely derived from plants, the biomass degree is theoretically 20%. To increase the biomass degree beyond that, the terephthalic acid must also be derived from plants, which would increase the effect of reducing the environmental load but would increase production costs. The ethylene glycol component and the terephthalic acid component may be a combination of petroleum-derived components and plant-derived components.
[0030] The lower limit of the biomass degree of the polyester constituting the film is preferably 5%, more preferably 10%, and even more preferably 13%, from the viewpoint of realizing the effect of reducing the environmental load. By having a biomass degree of 5% or more, the effect of reducing the environmental load can be expected. On the other hand, when only considering the reduction of the environmental load, the higher the upper limit of the biomass degree, the more preferable, and the upper limit is 100%. However, from the viewpoint of achieving both the production cost and the reduction of the environmental load, it is practically preferable that the biomass degree is 20% or less.
[0031] As a known method for analyzing the presence or absence of biomass raw materials, for example, the carbon isotope method ( 14 C) is used.
[0032] The recycled raw material is a raw material that is obtained by recovering and reusing polyester resin that has been made into a chemical product once or several times. Examples of chemical products from which the recycled raw material for the release film of the present invention is obtained include uncoated portions at both ends in the width direction cut and removed in the manufacturing process of the release film of the present invention, other recovered polyester films, and polyester resin products that have been distributed in a form other than a film, such as PET bottles.
[0033] When the release film of the present invention contains recycled materials, the content thereof is preferably 90% by mass or less in 100% by mass of the polyester resin in the release film. By limiting the use of recycled materials to 90% by mass or less, the amount of highly crystalline polyester that was once a chemical product is reduced, so that the thermal properties and transparency of the resulting release film can be reduced, and coloring can be reduced. The recycled materials may be used in either the polyester resin substrate or the release layer, but from the viewpoint of reducing the influence on the counterpart member, it is preferable to use them in the polyester resin substrate rather than in the release layer that is bonded to the counterpart member.
[0034] The polyester resin substrate layer of the release film is preferably a biaxially oriented polyester film from the viewpoint of thermal stability and mechanical strength. The biaxially oriented polyester film refers to a polyester film that shows a pattern oriented in two orthogonal directions in wide-angle X-ray diffraction. In general, a biaxially oriented polyester film is obtained by stretching an unstretched polyester sheet in two orthogonal directions. More specifically, for example, an unstretched polyester sheet is stretched about 2.5 to 5.0 times in each of the longitudinal and transverse directions, and then heat-treated to complete crystal orientation. By using a biaxially oriented polyester film as the polyester resin substrate, the thermal stability, particularly the dimensional stability and mechanical strength of the release film are improved, and the planarity is also improved. Here, the longitudinal direction refers to the direction in which the film runs during the manufacturing process (in the case of a film roll, this corresponds to the winding direction of the film), and the transverse direction refers to the direction perpendicular to the longitudinal direction within the film plane.
[0035] In addition, the polyester resin substrate layer may contain various additives, such as antioxidants, heat stabilizers, weather stabilizers, ultraviolet absorbers, organic lubricants, pigments, dyes, organic or inorganic fine particles, fillers, antistatic agents, nucleating agents, etc., to the extent that the properties of the layer are not deteriorated.
[0036] The thickness of the polyester resin substrate layer is not particularly limited and is appropriately selected depending on the application and type, but is usually preferably 5 to 500 μm, more preferably 10 to 250 μm, and particularly preferably 15 to 150 μm from the viewpoints of realizing sufficient mechanical strength, improving handleability, etc. The polyester resin substrate may be a single-layer film or a composite film obtained by coextrusion.
[0037] The release layer in the release film of the present invention is located on at least one side of the polyester resin substrate layer. The release layer is a layer necessary for easy peeling in a step of peeling the release film from a laminate after laminating a mating member such as a molten resin, an adhesive layer, or a surface coating layer thereon.
[0038] From the viewpoint of quality and releasability, the release layer in the release film of the present invention preferably has a film thickness of 20 nm or more and 400 nm or less, more preferably 30 nm or more and 200 nm or less. By making the film thickness of the release layer 20 nm or more and less than 400 nm, it becomes easy to provide a release layer having uniform coating property and releasability on the polyester film which becomes the polyester resin substrate layer. By making the film thickness of the release layer 400 nm or less, it is possible to suppress an increase in manufacturing cost, and also to reduce unevenness and streaks which occur when applying the resin composition for forming the release layer to the polyester film, and the quality of the obtained release film can be maintained good.
[0039] Hereinafter, the resin composition for forming the release layer of the release film of the present invention will be described. The release layer of the release film of the present invention is preferably formed from a resin composition containing a release agent (A) and at least one binder resin (B) selected from polyester resins, acrylic resins, and urethane resins, or a resin composition containing at least one reactive compound (C) selected from oxazoline compounds and isocyanate compounds in addition to these. By using such a composition and further adjusting the type and amount of each component to a suitable range, the surface free energy of the release layer and the ratio γh / γp of the polar force γp and the hydrogen bond force γh are adjusted to a suitable range, and not only is the release layer provided with good releasability from the counterpart member, but it is also easy to provide excellent control of the peel force due to heating (i.e., to impart a property that allows the counterpart member to be peeled off with a light force even after heating).
[0040] The release agent (A) in the release film of the present invention refers to a compound that can impart releasability (i.e., a property that reduces the surface free energy of the resin and facilitates peeling from the mating member) to the surface of the release layer. Examples of the release agent (A) that can be used in the release film of the present invention include long-chain alkyl group-containing resins, olefin resins, fluorine compounds, and wax-based compounds. Among them, long-chain alkyl group-containing resins are preferred in that they can impart good release properties to the release film. In addition, when a long-chain alkyl group-containing resin is used as the release agent (A), it is preferable that the release agent contains a reactive functional group as a side chain in addition to the long-chain alkyl group from the viewpoint of adjusting the ratio γh / γp of the polar force γp and the hydrogen bond force γh in the release layer to a preferred range. That is, a copolymer resin having a long-chain alkyl group and a reactive functional group is particularly preferred as the release agent of the present invention. Examples of the reactive functional group include a hydroxyl group, a carboxyl group, an amino group, a glycidyl group, an isocyanate group, a vinyl group, an acrylic group, and a methacrylic group, but from the viewpoint of compatibility with water, which is a preferred solvent described later, a hydroxyl group is preferred.
[0041] The long-chain alkyl group-containing resin may be a commercially available product. Specifically, the "Ashioresin" (registered trademark) series, which is a long-chain alkyl compound manufactured by Asio Sangyo Co., Ltd., the "Peiroil" series, which is a long-chain alkyl compound manufactured by Ipposha Yushi Kogyo Co., Ltd., and the "Rezem" series, which is an aqueous dispersion of a long-chain alkyl compound manufactured by Chukyo Yushi Co., Ltd., may be used. The long-chain alkyl group-containing resin used as the release agent (A) preferably has an alkyl group having 12 or more carbon atoms, and more preferably has an alkyl group having 16 or more carbon atoms. By making the carbon number of the alkyl group 12 or more, the hydrophobicity is increased, and sufficient release performance can be imparted to the release layer. The upper limit of the carbon number of the alkyl group is not particularly limited, but it is preferable that it is 25 or less because it is easy to manufacture.
[0042] The resin having an alkyl group having 12 or more carbon atoms is more preferably a resin having a side chain of an alkyl group having 12 or more carbon atoms on the main chain of polymethylene. By having a main chain of hydrophobic polymethylene, even when a copolymer resin of the above-mentioned long-chain alkyl group and reactive functional group is formed, aggregation of the reactive functional group can be suppressed, and the release effect of the release agent (A) can be improved.
[0043] Another preferred embodiment of the release agent (A) is a random copolymer having an alkyl group with 12 or more carbon atoms (more preferably a vinyl alcohol-based random copolymer having an alkyl group with 12 or more carbon atoms). This embodiment also makes it easy to set γh / γp within a suitable range, and the release effect of the release agent (A) can be made more excellent even after heating.
[0044] The presence or absence of alkyl groups having 12 or more carbon atoms in the release layer can be evaluated from the release film, for example, by using the intensity of the signal corresponding to the alkyl group obtained by TOF-SIMS (TOF-SIMS: time-of-flight secondary ion mass spectrometry). At this time, by combining the cutting method using ion sputtering, it is possible to perform continuous measurements in the depth direction (thickness direction), and the distribution state of the alkyl group-containing compound can also be evaluated.
[0045] As the binder resin (B) forming the release layer in the release film of the present invention, it is more preferable to use a polyester resin from the viewpoint of adjusting the ratio γh / γp of the polar force γp and the hydrogen bond force γh, which is a parameter that facilitates the control of the coating property and the peeling force by heating, and from the viewpoint of ease of introduction of reactive functional groups. Examples of reactive functional groups include sulfoisophthalic acid (SSIA) groups, hydroxyl groups, carboxyl (COOH) groups, amino groups, glycidyl groups, isocyanate groups, vinyl groups, acrylic groups, and methacrylic groups, and from the viewpoint of controlling the peeling force by heating by adjusting the ratio γh / γp of γp and γh, it is preferable to have at least one of an SSIA group and a carboxyl group. That is, in the release film of the present invention, it is preferable that the release layer contains a polyester resin having at least one of an SSIA group and a COOH group.
[0046] The polyester resin used as the binder resin (B) in the release film of the present invention has an ester bond in the main chain or side chain, and is preferably obtained by polycondensation of a dicarboxylic acid and a diol. As the dicarboxylic acid that is the raw material of the polyester resin, aromatic, aliphatic, and alicyclic dicarboxylic acids can be used. As the aromatic dicarboxylic acid, terephthalic acid, isophthalic acid, orthophthalic acid, phthalic acid, 2,5-dimethylterephthalic acid, 1,4-naphthalenedicarboxylic acid, biphenyldicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,2-bisphenoxyethane-p-p'-dicarboxylic acid, phenylindanedicarboxylic acid, and the like can be used. As the aliphatic and alicyclic dicarboxylic acids, succinic acid, adipic acid, sebacic acid, azelaic acid, dodecanedioic acid, dimer acid, 1,3-cyclopentanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and the like, and their ester-forming derivatives can be used. These may be used alone or in combination of two or more kinds.
[0047] Examples of diol components that are raw materials for the polyester resin include ethylene glycol, diethylene glycol, polyethylene glycol, propylene glycol, polypropylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 2,4-dimethyl-2-ethylhexane-1,3-diol, neopentyl glycol, 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2,2,4-trimethyl- 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, 4,4'-thiodiphenol, bisphenol A, 4,4'-methylenediphenol, 4,4'-(2-norbornylidene)diphenol, 4,4'-dihydroxybiphenol, o-, m-, and p-dihydroxybenzene, 4,4'-isopropylidenephenol, 4,4'-isopropylidenebindiol, cyclopentane-1,2-diol, cyclohexane-1,2'-diol, cyclohexane-1,2-diol, cyclohexane-1,4-diol, etc. can be used. These may be used alone or in combination.
[0048] Furthermore, as the binder resin (B), it is also possible to use modified polyester copolymers, for example, block copolymers and graft copolymers modified with acrylic, urethane, epoxy, or the like.
[0049] The acrylic resin that can be used as the binder resin (B) is not particularly limited, and examples of monomer components that constitute the acrylic resin include alkyl acrylates, alkyl methacrylates (alkyl groups include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, t-butyl, 2-ethylhexyl, lauryl, stearyl, cyclohexyl, phenyl, benzyl, and phenylethyl groups), hydroxyl group-containing monomers such as 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, and 2-hydroxypropyl methacrylate, acrylamide, and methacrylamide. Amide group-containing monomers such as N-methylacrylamide, N-methylmethacrylamide, N-methylolacrylamide, N-methylolmethacrylamide, N,N-dimethylolacrylamide, N-methoxymethylacrylamide, N-methoxymethylmethacrylamide, and N-phenylacrylamide, amino group-containing monomers such as N,N-diethylaminoethylacrylate and N,N-diethylaminoethylmethacrylate, epoxy group-containing monomers such as glycidyl acrylate and glycidyl methacrylate, and monomers containing a carboxyl group or a salt thereof such as acrylic acid, methacrylic acid, and salts thereof (lithium salt, sodium salt, potassium salt, etc.) can be used. These monomers may be polymerized alone or may be copolymerized in combination with other types of monomers.
[0050] The urethane resin used as the binder resin (B) is not particularly limited, but is preferably a resin obtained by reacting a polyhydroxy compound with a polyisocyanate compound by a known urethane resin polymerization method such as emulsion polymerization or suspension polymerization.
[0051] Examples of polyhydroxy compounds include polyethylene glycol, polypropylene glycol, polyethylene propylene glycol, polytetramethylene glycol, hexamethylene glycol, tetramethylene glycol, 1,5-pentanediol, diethylene glycol, triethylene glycol, polycaprolactone, polyhexamethylene adipate, polyhexamethylene sebacate, polytetramethylene adipate, polytetramethylene sebacate, trimethylolpropane, trimethylolethane, pentaerythritol, polycarbonate diol, and glycerin.
[0052] Examples of the polyisocyanate compound that can be used include hexamethylene diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, isophorone diisocyanate, an adduct of tolylene diisocyanate and trimethylenepropane, and an adduct of hexamethylene diisocyanate and trimethylolethane.
[0053] The reactive compound (C) that forms the release layer in the release film of the present invention preferably contains at least one compound selected from oxazoline compounds and isocyanate compounds, from the viewpoint of adjusting the ratio γh / γp of the polar strength γp to the hydrogen bonding strength γh, which is a parameter that facilitates control of the peel force due to heating. Among these, oxazoline compounds are particularly preferred because they are more likely to form crosslinks with SSIA groups and COOH groups.
[0054] An oxazoline compound that can be suitably used as the reactive compound (C) has an oxazoline group as a functional group in the compound, and is preferably an oxazoline group-containing copolymer obtained by copolymerizing at least one monomer containing an oxazoline group and at least one other monomer.
[0055] As the monomer containing an oxazoline group, 2-vinyl-2-oxazoline, 2-vinyl-4-methyl-2-oxazoline, 2-vinyl-5-methyl-2-oxazoline, 2-isopropenyl-2-oxazoline, 2-isopropenyl-4-methyl-2-oxazoline, and 2-isopropenyl-5-ethyl-2-oxazoline can be used, and one or a mixture of two or more of these can also be used. Among them, 2-isopropenyl-2-oxazoline is suitable because it is easily available industrially.
[0056] In the oxazoline compound, at least one other monomer used for the monomer containing an oxazoline group is a monomer copolymerizable with the monomer containing an oxazoline group, and examples thereof include acrylic acid esters or methacrylic acid esters such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylhexyl acrylate, and 2-ethylhexyl methacrylate, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, and maleic acid, acrylonitrile, and methacrylonitrile. Any unsaturated nitriles, unsaturated amides such as acrylamide, methacrylamide, N-methylol acrylamide, N-methylol methacrylamide, vinyl esters such as vinyl acetate, vinyl propionate, vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, olefins such as ethylene, propylene, halogen-containing α,β-unsaturated monomers such as vinyl chloride, vinylidene chloride, vinyl fluoride, α,β-unsaturated aromatic monomers such as styrene and α-methylstyrene, and the like can be used alone or in a mixture of two or more of these.
[0057] As the oxazoline compound, commercially available products can be used, and examples of compounds that can be suitably used include "Epocross" (registered trademark) WS-300, WS-500, WS-700, etc., manufactured by Nippon Shokubai Co., Ltd.
[0058] Examples of isocyanate compounds that can be used as the reactive compound (C) include tolylene diisocyanate, diphenylmethane-4,4'-diisocyanate, meta-xylylene diisocyanate, hexamethylene-1,6-diisocyanate, 1,6-diisocyanatehexane, an adduct of tolylene diisocyanate and hexanetriol, an adduct of tolylene diisocyanate and trimethylolpropane, polyol-modified diphenylmethane-4,4'-diisocyanate, carbodiimide-modified diphenylmethane-4,4'-diisocyanate, isophorone diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-bitrylene-4,4' diisocyanate, 3,3'dimethyldiphenylmethane-4,4'-diisocyanate, and metaphenylene diisocyanate.
[0059] Furthermore, since isocyanate groups easily react with water, in terms of the pot life of the coating agent, it is preferable to use blocked isocyanate compounds in which the isocyanate groups are masked with a blocking agent, etc. In this case, when heat is applied in the drying process after the resin composition for forming the release layer is applied to the polyester film that becomes the polyester resin substrate layer, the blocking agent is dissociated and the isocyanate groups are exposed, which causes the crosslinking reaction to proceed.
[0060] As the isocyanate compound, commercially available products can be used, and examples of suitable isocyanate compounds include "Elastron" (registered trademark) BN-69, BN-77, E-37, etc., manufactured by Daiichi Kogyo Seiyaku Co., Ltd. These are blocked isocyanate compounds.
[0061] The preferred contents of the release agent (A), the binder resin (B), and the reactive compound (C) in the resin composition for forming the release layer of the release film of the present invention will be described later.
[0062] The resin composition for forming the release layer may contain a solvent or a dispersion medium (hereinafter, abbreviated as a solvent). That is, various components may be dissolved or dispersed in a solvent to form a resin composition, which may be applied to a polyester film that will become a polyester resin substrate layer. When such a method is adopted, a release film having a release layer laminated thereon can be obtained by drying the solvent after application and heating.
[0063] In the release film of the present invention, it is preferable to use an aqueous solvent as the solvent for the resin composition for forming the release layer. Here, the aqueous solvent refers to a mixture of water or water and an organic solvent soluble in water, such as alcohols such as methanol, ethanol, isopropyl alcohol, butanol, ketones such as acetone, methyl ethyl ketone, glycols such as ethylene glycol, diethylene glycol, propylene glycol, etc., mixed in any ratio. By using an aqueous solvent, not only can the rapid evaporation of the solvent during the heating process be suppressed to form a uniform release layer, but it is also excellent in terms of environmental load.
[0064] In the release film of the present invention, the resin composition for forming the release layer can be prepared by mixing and stirring the release agent (A), which is water-dispersed or water-soluble as necessary, the binder resin (B), the reactive compound (C) and the aqueous solvent in any order and at a desired weight ratio (the reactive compound (C) is optional). Next, various additives such as a lubricant, inorganic particles, organic particles, surfactants, antioxidants, and thermal initiators can be mixed and stirred in any order as needed to the extent that they do not deteriorate the properties of the release layer provided by the resin composition. The mixing and stirring method can be a method of shaking the container by hand, a method of stirring with a magnetic stirrer or stirring blade, a method of using ultrasonic irradiation, vibration dispersion, or the like.
[0065] In the resin composition for forming the release layer in the present invention, the release agent (A) has a preferred content. Specifically, when the entire release layer (the total of the release agent (A), the binder resin (B), and the reactive compound (C) in the resin composition for forming the release layer) is taken as 100% by mass, the release agent (A) is preferably 8% by mass or more and 50% by mass or less, more preferably 8% by mass or more and 30% by mass or less, particularly preferably 8% by mass or more and 25% by mass or less, and most preferably 10% by mass or more and 25% by mass or less. When the release agent (A) is 8% by mass or more, the release property of the release layer is at a sufficient level. On the other hand, when the release agent (A) is 50% by mass or less, the coating property is improved and the falling off of the release agent (A) from the release film is reduced, and the contamination of the counterpart member by the release agent (A) can be suppressed.
[0066] There is also a preferred range for the content of the binder resin (B). Specifically, when the entire release layer (the total of the release agent (A), the binder resin (B), and the reactive compound (C) in the resin composition for forming the release layer) is taken as 100% by mass, the binder resin (B) is preferably 10% by mass or more, more preferably 45% by mass or more, and particularly preferably 60% by mass or more. When the binder resin (B) satisfies the above content, it becomes easier to control the ratio γh / γp of the polar force γp and the hydrogen bond force γh in the release film within a preferred range, and it becomes easier to control the peeling force by heating. On the other hand, the upper limit of the content depends on the blending amount of the release agent (A) and the reactive compound (C), but is preferably 92% by mass, more preferably 90% by mass.
[0067] On the other hand, the reactive compound (C) is an optional component, but when added, it is possible to adjust the compounding ratio so that the above-mentioned release agent (A) and binder resin (B) have preferred contents.
[0068] The method for producing the release film of the present invention will be described below. The method for producing the release film of the present invention is characterized in that it comprises, in this order, a coating step of coating at least one side of a polyester resin substrate sheet with a resin composition for forming a release layer, a stretching step of stretching the polyester resin substrate sheet after the resin composition is applied in at least one axial direction, and a heat treatment step of heating the polyester resin substrate sheet after the stretching to 150 ° C. or more to form a release layer. That is, in the method for producing the release film of the present invention, an in-line coating method is adopted in which the resin composition is applied within the polyester film production process. The release film of the present invention can also be produced by an off-coating method in which a resin composition is applied to a film after film formation, but by using the in-line coating method, it becomes easy to make the release layer more uniformly thin and to improve the heat resistance of the release film and the peelability before and after heating. Here, the polyester resin substrate sheet refers to a polyester film that becomes a polyester resin substrate layer when it becomes a release film, and the resin composition for forming a release layer is a coating composition that forms a release layer when it becomes a release film.
[0069] The method for producing a release film of the present invention includes a coating step of coating at least one surface of a polyester resin substrate sheet with a resin composition for forming a release layer. In the coating step, the above-mentioned preferred resin composition for forming a release layer is coated, and this resin composition becomes a release layer by heating in the subsequent heat treatment step. The resin composition for forming a release layer used here may contain, in addition to the above-mentioned release agent (A) and binder resin (B), the above-mentioned reactive compound (C), crosslinking catalyst, lubricant, inorganic particles, organic particles, surfactants, antioxidants, thermal initiators, and other various additives.
[0070] The method for producing a release film of the present invention includes a stretching step of stretching the polyester resin substrate sheet after coating with the resin composition in at least one axial direction. In such an embodiment, the resin composition is applied before the stretching, so that the method for coating the resin composition for forming the release layer is an in-line coating method. In the method for producing a release film of the present invention, the stretching is performed after the coating step, so that the resin composition for forming the release layer is coated on a substantially amorphous unstretched (unoriented) polyester film (hereinafter sometimes referred to as A film) obtained by melt extrusion and then quenching, a uniaxially stretched (uniaxially oriented) polyester film (hereinafter sometimes referred to as B film) that is then stretched in the longitudinal direction, or a biaxially stretched (biaxially oriented) polyester film before heat treatment that is further stretched in the width direction (these correspond to polyester resin substrate sheets).
[0071] A resin composition for forming a release layer is applied to either the A film or the B film before the crystal orientation is completed, the solvent is evaporated, and then the A film or the B film is stretched in a uniaxial or biaxial direction, so that the polyester film can be produced, the resin composition is applied, the solvent is dried, and the heat treatment (i.e., the formation of the release layer) can be performed in a continuous process. Therefore, not only is there an advantage in terms of manufacturing cost, but by completing the crystal orientation of the polyester resin substrate after drying, it is possible to perform a high-temperature heat treatment on the release layer while reducing the deformation and heat shrinkage of the polyester film. As a result, the release film is less likely to undergo deformation such as shrinkage during the heat treatment in the subsequent processing, so that excellent releasability can be obtained even with respect to the mating member that requires a processing process at a high temperature. Furthermore, the stretching after application has the advantage that it is easy to make the release layer more uniformly thin.
[0072] The method for producing a release film of the present invention includes a heat treatment step in which the polyester resin substrate sheet after stretching is heated to 150°C or higher to form a release layer. The heat treatment applied to the coating layer has a preferable temperature condition from the viewpoint of sufficiently advancing the crosslinking reaction of the release layer described above and suppressing the penetration of the water-based coating agent. Specifically, the heat treatment temperature is 170°C or higher, preferably 200°C or higher, and more preferably 220°C or higher. The upper limit of the heat treatment temperature is preferably 260°C from the viewpoint of the heat resistance of the polyester resin substrate sheet, and more preferably 250°C from the viewpoint of the heat resistance of the resin composition for forming the release layer. By setting the heat treatment temperature to 260°C or lower, deformation of the polyester film is suppressed and thermal decomposition of the resin composition is reduced, making it easier to obtain a release film with a more uniform release layer.
[0073] Among them, as a method for producing the release film of the present invention, a method in which a resin composition for forming a release layer is applied to a film (B film) uniaxially stretched in the longitudinal direction, the solvent is dried, and then the film is stretched in the width direction and heated is excellent. This method is because, compared with a method in which a resin composition for forming a release layer is applied to an unstretched film (A film) and then biaxially stretched, the layer formed by the resin composition for forming a release layer undergoes one less stretching step, so that defects and cracks in the release layer due to stretching are unlikely to occur, and a release layer with excellent transparency and smoothness can be formed.
[0074] On the other hand, the case where an offline coating method is used instead of the method for producing the release film of the present invention will be described. The offline coating method is a method in which the above-mentioned A film is stretched uniaxially or biaxially, and the crystal orientation of the polyester film is completed by performing a heat treatment, or the A film itself is coated with a resin composition for forming a release layer in a process separate from the film production process. In other words, it is a coating method in which stretching is not performed after coating. In the production of the release film of the present invention, it is preferable to use the in-line coating method from the various advantages described above, but even when the release layer is formed by the offline coating method, the processing temperature is 170 ° C. or more, and preferably 200 ° C. or more. By setting the processing temperature to 170 ° C. or more, the thin release layer is sufficiently cured, so that the adhesion between the release layer and the polyester resin substrate layer is good, and the releasability before and after heating can be improved. In addition, the upper limit of the processing temperature is preferably 260 ° C. from the perspective of the heat resistance of the polyester resin substrate sheet. By setting the processing temperature to 260 ° C. or less, deformation of the polyester resin substrate sheet is suppressed, making it easier to obtain a more uniform release film.
[0075] Here, the method of applying the resin composition for forming a release layer to the polyester resin substrate sheet can be any known application method, such as an in-line coating method or an offline coating method, such as a bar coating method, a reverse coating method, a gravure coating method, a die coating method, or a blade coating method.
[0076] Next, the method for producing the release film of the present invention will be explained in more detail using an in-line coating method in which a polyethylene terephthalate (hereinafter, PET) film is used as the polyester film as an example, but the method for producing the release film of the present invention is not limited thereto.
[0077] First, PET pellets are thoroughly vacuum dried, then fed to an extruder, melt-extruded into a sheet at 260°C to 280°C, and cooled to solidify to produce an unstretched (unoriented) PET film (A film). This film is stretched 2.5 to 5.0 times in the longitudinal direction with a roll heated to 80 to 120°C to obtain a uniaxially oriented PET film (B film). The aforementioned resin composition for forming the release layer, adjusted to a predetermined concentration, is applied to one side of this B film.
[0078] At this time, before applying the resin composition for forming the release layer, the surface of the B film to be coated may be subjected to a surface treatment such as a corona discharge treatment. By performing a surface treatment such as a corona discharge treatment, the wettability of the resin composition for forming the release layer to the B film is improved, so that the repelling can be reduced and a release layer with a more uniform coating thickness can be formed on the B film surface. After application, the B film is held at both ends in the width direction with clips and guided to a heat treatment zone (preheating zone) at 80 to 130 ° C., where the solvent of the resin composition for forming the release layer is dried. After drying, the B film is stretched 1.1 to 5.0 times in the width direction, and then guided to a heat treatment zone (thermal fixation zone) at 150 to 260 ° C., preferably 170 to 260 ° C., where heat treatment is performed for 1 to 30 seconds, and crystal orientation is completed.
[0079] In this heat treatment step (heat setting step), a relaxation treatment of 3 to 15% may be performed in the width direction or length direction as necessary. The release film thus obtained is a release film with excellent applicability, adhesion, and transparency for water-based coating materials.
[0080] In addition, the release film of the present invention may have an intermediate layer between the release layer and the polyester resin substrate layer, but when an intermediate layer is provided, the film may be scratched when the film having the intermediate layer laminated thereon is wound up or in the subsequent process up to the provision of the release layer of the present invention. Therefore, in the present invention, it is preferable that the release layer and the resin substrate layer are directly laminated.
[0081] There is no limitation to the configuration of the polyester resin substrate layer constituting the release film of the present invention, and examples thereof include a single layer configuration consisting of only Layer A, a laminate configuration of Layer A / Layer B, i.e., a two-type two-layer laminate configuration, a laminate configuration of Layer A / Layer B / Layer A, i.e., a two-type three-layer laminate configuration, a laminate configuration of Layer A / Layer B / Layer C, i.e., a three-type three-layer laminate configuration, etc. Note that Layer A, Layer B, and Layer C herein all contain polyester resin as a main component, but have different compositions.
[0082] The method of laminating the resin substrate layer constituting the release film of the present invention is not particularly limited, and examples thereof include lamination methods using a coextrusion method, lamination methods using lamination by bonding, and combinations thereof. From the viewpoint of transparency and manufacturing stability, it is preferable to adopt a coextrusion method. When forming a laminated structure, different resin structures may be used to impart different functions to each layer. For example, when forming a laminated structure of A layer / B layer / A layer, that is, a two-kind three-layer laminate structure, a method of forming B layer from homopolyethylene terephthalate from the viewpoint of transparency, and adding particles to A layer to impart easy slippage, etc., can be mentioned. The laminate of the present invention preferably has an adhesive layer on the release layer side of the release film. The laminate of the present invention preferably has a release layer on one surface of the release film, and an adhesive layer on the release layer side. As the adhesive layer, various tackifiers are used. For example, acrylic resins, terpene resins, phenolic resins, terpene phenolic resins, silicone resins, coumarone resins, rosin compounds (rosin or rosin esters, esters of hydrogenated rosin), petroleum resins, xylene resins, or styrene resins can be mentioned. Although not particularly limited, acrylic adhesives are preferably used. EXAMPLES
[0083] The release film of the present invention will be described in detail below based on specific examples, but the present invention is not limited to these examples.
[0084] <Methods for measuring characteristics and evaluating effects> The methods for measuring the characteristics and evaluating the effects of the present invention are as follows.
[0085] (1) Method for analyzing the composition of the release layer surface The composition of the release layer surface of the release film was analyzed using GCIB-TOF-SIMS (GCIB: gas cluster ion beam, TOF-SIMS: time-of-flight secondary ion mass spectrometry). The measurement conditions were as follows. <Sputtering conditions> Ion source: Argon gas cluster ion beam <Detection conditions> Primary ion: Bi3 ++ (25keV) Secondary ion polarity: positive Mass range: m / z 0~1000 Measurement range: 200 x 200 μm 2 The peak intensity of the positive ion fragment detected at the maximum intensity in the measurement is K, and the peak intensity of the positive ion fragment derived from polydimethylsiloxane (SiCH + The peak intensity of the fragment ion (M / Z=43) was taken as P, and the ratio P / K was calculated. When P / K is less than 0.01, it was determined that the release layer did not substantially contain a silicone compound. Furthermore, the fragment of the positive ion derived from methylolmelamine (C6H7N6 + The peak intensity of the fragment ion (M / Z=163) was taken as F, and the ratio F / K was calculated. When F / K<0.0005, it was determined that the release layer did not substantially contain methylolmelamine.
[0086] (2) Calculation method of surface free energy, polarity, and hydrogen bonding strength First, the release film was left for 24 hours in an atmosphere at room temperature of 23°C and relative humidity of 65%. After that, under the same atmosphere, the contact angles of four types of solutions, pure water, ethylene glycol, formamide, and diiodomethane, were measured at five points on the surface side of the release layer of the release film using a contact angle diameter DropMaster DM-501 manufactured by Kyowa Interface Science Co., Ltd. The average value of the three measured values excluding the maximum and minimum values of the five measured values was used as the contact angle of each solution. Next, using the contact angles of the four types of solutions obtained, the formula "Deciding the surface free energy of a solid (γ) with the dispersion force component (γ S d ), polar force component (γ S p ), and hydrogen bonding strength component (γ S h The dispersion force, polar force, hydrogen bonding force, and surface free energy, which is the sum of the dispersion force and the polar force, were calculated by the geometric mean method based on the extended Fowkes equation. The specific calculation method and the meaning of each symbol are described below. γ S L When is the tension at the interface between a solid and a liquid, equation (1) holds true. Gamma S L : Surface free energy of solids and known solutions listed in Table 1 Gamma S : Surface free energy of a solid Gamma L : Surface free energy of known solutions listed in Table 1 Gamma S d : Dispersion force component of the surface free energy of a solid Gamma S p : Polar force component of the surface free energy of a solid Gamma S h : Hydrogen bond force component of the surface free energy of a solid Gamma L d : Dispersion force components of the surface free energy of known solutions listed in Table 1 Gamma L p: Polar component of surface free energy of known solutions listed in Table 1 Gamma L h : Hydrogen bond force component of surface free energy of known solutions listed in Table 1 Gamma S L =γ S +γ L -2(γ S d ·γ L d ) 1 / 2 -2(γ S p ·γ L p ) 1 / 2 -2(γ S h ·γ L h ) 1 / 2 Formula (1). Furthermore, the state when a droplet is in contact with a smooth solid surface at a contact angle (θ) is expressed by the following equation (Young's equation). Gamma S =γ S L +γ L cosθ ··· Equation (2). Combining equations (1) and (2), we obtain the following equation. (γ S d ·γ L d ) 1 / 2 +(γ S p ·γ L p ) 1 / 2 +(γ S h ·γ L h ) 1 / 2 =γ L (1+cosθ) / 2 Equation (3). In practice, the contact angle (θ) and the surface tension components (γ L d , γ L p , γ Lh ) into equation (3) and solve the four simultaneous equations. As a result, the surface free energy of the solid (γ), the dispersion force component (γ S d ), polar force component (γ S p ), and hydrogen bonding strength component (γ S h In practice, the release layer of the release film is used as a solid, so the surface free energy (γ) and dispersion force component (γ S d ), polar force component (γ S p ), and hydrogen bonding strength component (γ S h ) are the surface free energy (γ), the dispersion force component (γd), the polar force component (γp), and the hydrogen bonding force component (γh) of the release layer, respectively.
[0087] [Table 1]
[0088] (3) Initial tape peel strength The initial tape peeling force was measured as follows. First, an acrylic polyester adhesive tape (Nitto Denko Corporation, Nitto 31B tape, 19 mm width) was attached to the release layer of the release film, and a 2 kgf roller was moved back and forth once from above to prepare a tape-attached release film. After that, the tape-attached release film was left to stand for 24 hours in an environment of 23°C and 65% RH, and then the peeling force (N / 19 mm) was measured at a peeling angle of 180° and a tensile speed of 300 mm / min using a peeling analyzer "VPA-2" manufactured by Kyowa Interface Science Co., Ltd. From the graph of peeling force (N / 19 mm) vs. travel distance (mm) obtained by the measurement, the average peeling force at 10 to 40 mm was calculated. This measurement was performed five times, and the average of the three measurements excluding the maximum and minimum values was taken as the peeling force of the release film (N / 19 mm). This value was converted to N / 50 mm to obtain the initial tape peeling force (i.e., [initial tape peeling force (N / 50 mm)] = [peeling force (N / 19 mm)] / 19 x 50).
[0089] (4) Tape peel strength after heating at 50°C for 1 hour The tape peeling force after heating at 50°C for 1 hour was measured as follows: First, a tape-attached release film was prepared as described in "(3) Initial tape peeling force", and the tape-attached release film was heated in a hot air oven at 50°C for 1 hour instead of being left to stand in an environment of 23°C and 65% RH for 24 hours, and the tape peeling force was measured in the same manner as "(3) Initial tape peeling force".
[0090] (5) Initial adhesive layer peel strength evaluation An acrylic adhesive (manufactured by Soken Chemical Industries, "SK Dyne" (registered trademark) 1435) was diluted with ethyl acetate, toluene, and methyl ethyl ketone (MEK) so that the solid content of the adhesive was 25%, and 2.0 parts by mass of a curing agent (manufactured by Nippon Polyurethane Industry Co., Ltd., "Coronate" (registered trademark) D-90) was mixed with 100 parts by mass of the solid content of the adhesive, and the coating was applied to the release layer of the release film using an applicator so that the final thickness was 40 μm. Then, the adhesive was dried in a hot air oven at 80 ° C. for 1 minute to form an adhesive laminated sheet. An acrylic polyester adhesive tape (manufactured by Nitto Denko Corporation, Nitto 31B tape, 19 mm wide) was attached as a support on the adhesive layer of the adhesive laminated sheet, and the peeling force was measured in the same manner as in "(3) Initial tape peeling force". From the obtained results, evaluation was performed according to the following criteria. ○ was good, and △ was a level that was not problematic in practical use. ○: Initial adhesive layer peel strength less than 6.0N / 50mm △: Initial adhesive layer peel strength 6.0N / 50mm or more and less than 8.0N / 50mm ×: Initial adhesive layer peel strength of 8.0 N / 50 mm or more.
[0091] (6) Evaluation of adhesive layer peel strength after heating The adhesive laminated sheet described in "(5) Initial adhesive layer peel strength" was further heat-treated in a hot air oven at 150°C for 30 minutes, and the peel strength was measured in the same manner as "(3) Initial tape peel strength".
[0092] (7) Evaluation of adhesive layer peelability after heating From the peel strengths calculated in the sections "(5) Initial adhesive layer peel strength" and "(6) Adhesive layer peel strength after heating", the difference in adhesive layer peel strength before and after heating (Δ peel strength) was calculated using the following formula, and the following evaluations were performed. A was evaluated as good, and Δ was evaluated as a level that was acceptable for practical use. [ΔPeeling strength] = Peeling strength of adhesive layer after heating / Initial peeling strength of adhesive layer ○: Δ peel force less than 1.5 △: Δ peel strength 1.5 or more and less than 2.0 ×: Δ peel force of 2.0 or more.
[0093] (8) Adhesive application properties The adhesive having the composition shown in the section "(5) Initial adhesive layer peel strength" was applied to the release layer of the release film of the present invention with an applicator to three final thicknesses (40 μm, 10 μm, 1 μm), and then dried in a hot air oven at 100°C for 5 minutes to form an adhesive laminated film. The adhesive laminated film was visually evaluated for the presence or absence of cissing. The adhesive coating property was considered to be good when it was rated as "○" or higher, and "△" was rated as a level that was not problematic in practical use. In general, the thinner the adhesive coating thickness, the more likely it is to cause cissing. ◯: No repelling was observed at any coating thickness. Δ: No repelling was observed at a coating thickness of 40 μm, but repelling was observed at least at either 10 μm or 1 μm. ×: Cracks were observed at all coating thicknesses.
[0094] (9) Receding contact angle of water The receding contact angle of water on the release layer was measured by the expansion-contraction method using a contact angle meter Drop Master DM-501 manufactured by Kyowa Interface Science Co., Ltd., according to the expansion-contraction method measurement manual for the device. First, the release film was left to stand for 24 hours in an atmosphere of room temperature 23°C and relative humidity 65%. Then, under the same atmosphere, a droplet of pure water with a droplet volume of 55 μL was once created on the surface side of the release layer of the release film, and then, with the tip of the syringe needle pointed at the droplet, it was continuously aspirated at a liquid discharge speed of 5.6 μL / s, and the shape of the droplet in the shrinking process was continuously photographed from the side of the droplet every 100 milliseconds from 5000 milliseconds after the start of suction, and the respective contact angles were calculated from each photographed image. The contact angle initially changes as the droplet shrinks, then becomes constant. The contact angle at that point was taken as the receding contact angle. The method for determining when the contact angle became constant was to arrange the contact angles calculated from images taken continuously every 100 milliseconds in order over time, select five consecutive points in that order, and take the average value when the standard deviation of the five consecutive points first became 1° or less as the receding contact angle θr for that measurement. This measurement was performed five times for one sample, and the average value of the three values excluding the maximum and minimum values was taken as the receding contact angle of water for that sample.
[0095] [Components used in the examples and comparative examples] In the examples and comparative examples, the components shown below were used.
[0096] <Release agent (A)> Release agent (A-1): Long-chain alkyl group-containing resin (1) (random copolymer) 200 parts by mass of xylene and 600 parts by mass of octadecyl isocyanate were added to a four-neck flask and heated under stirring. From the point when xylene started to reflux, 100 parts by mass of polyvinyl alcohol with an average degree of polymerization of 500 and a degree of saponification of 88 mol% were added little by little at 10-minute intervals over about 2 hours. After the addition of polyvinyl alcohol was completed, the mixture was refluxed for another 2 hours to terminate the reaction. Thereafter, the reaction mixture was cooled to about 80°C and added to methanol, and the resulting white precipitate was filtered off. 140 parts by mass of xylene was added to the obtained white precipitate, heated to completely dissolve it, and then methanol was added again to cause precipitation. This operation was repeated several times. The obtained precipitate was then washed with methanol, dried and pulverized to obtain a long-chain alkyl group-containing resin (vinyl alcohol-based random copolymer having an alkyl group with 18 carbon atoms (long-chain alkyl group-containing resin (1)). This was diluted with water to adjust to 20% by mass.
[0097] Release agent (A-2): Resin containing long-chain alkyl groups (2) (block copolymer) An aqueous dispersion of a long-chain alkyl group-containing resin (2) was obtained through the following steps (I) to (III).
[0098] Step (I): In a pressure-resistant glass polymerization ampoule, methyl methacrylate (MMA) (Kanto Chemical Co., Ltd.), α,α'-azobisisobutyronitrile (AIBN) (Kanto Chemical Co., Ltd.) as a polymerization initiator, cumyl dithiobenzoate (CDB) as a RAFT agent, and toluene as a solvent were charged in a mass ratio of MMA / CDB / AIBN / toluene = 2.92 / 0.03 / 0.007 / 2.27. Next, the mixed solution in the ampoule was degassed twice by the freeze degassing method, and then the ampoule was sealed and heated in an oil bath at 100 ° C for 18 hours to obtain a reaction solution containing polymer (I-1).
[0099] Step (II): Octadecyl acrylate, AIBN as a polymerization initiator, and toluene as a solvent were added to the reaction solution in the ampoule in a mass ratio of octadecyl acrylate / AIBN / toluene = 1.37 / 0.003 / 1.3 to obtain a polymerization solution, which was then subjected to freeze-degassing twice, and the ampoule was sealed and heated at 100°C for 48 hours. The polymerization solution was then dropped into 20 times the mass of hexane and stirred to precipitate a solid. The resulting solid was collected by filtration and vacuum-dried overnight at 40°C to obtain a long-chain alkyl group-containing resin (a block copolymer having an alkyl group with 18 carbon atoms (long-chain alkyl group-containing resin (2)).
[0100] Step (III): The obtained long-chain alkyl group-containing resin (2) was emulsified as follows to prepare an aqueous resin emulsion. 375 parts by mass of water was placed in a homomixer, and 45 parts by mass of polyoxyethylene nonylphenyl ether, 30 parts by mass of polyoxyethylene polyoxypropylene glycol, 200 parts by mass of long-chain alkyl group-containing resin (2), and 150 parts by mass of toluene were added in that order, heated to 70°C, and stirred uniformly. This mixture was transferred to a pressure homogenizer and emulsified, and then the pressure was reduced under heating to distill off the toluene.
[0101] Release agent (A-3): Silicone-containing resin "Simac" (registered trademark) US-480 manufactured by Toagosei Co., Ltd. (a silicone graft copolymer having an acrylic backbone, containing hydroxyl and carboxyl groups).
[0102] <Binder resin (B)> Binder resin (B-1): Polyester resin (containing SSIA group) An aqueous dispersion of a polyester resin having the following copolymer composition was prepared. (Dicarboxylic acid component) Terephthalic acid: 80 mol% Sodium dimethyl 5-sulfoisophthalate: 20 mol% (Diol component) Diethylene glycol: 15 mol% Ethylene glycol: 85 mol %.
[0103] Binder resin (B-2): Polyester resin (containing carboxyl groups) An aqueous dispersion of a polyester resin having the following copolymer composition was prepared. (Dicarboxylic acid component) Terephthalic acid: 80 mol% Trimellitic acid: 20 mol% (Diol component) Compound in which 2 moles of ethylene oxide are added to 1 mole of bisphenol S: 86 mole% Ethylene glycol: 14 mole %.
[0104] Binder resin (B-3): Polyester resin (containing carboxyl and SSIA groups) An aqueous dispersion of a polyester resin having the following copolymer composition was prepared. (Dicarboxylic acid component) Dimethyl 2,6-naphthalenedicarboxylate: 68 mol% Trimellitic acid: 20 mol% Sodium dimethyl 5-sulfoisophthalate: 12 mol% (Diol component) Compound in which 2 moles of ethylene oxide are added to 1 mole of bisphenol S: 86 mole% Ethylene glycol: 14 mole %.
[0105] Binder resin (B-4): Urethane resin "HYDRAN" (registered trademark) AP-40 (solid content concentration: 40% by mass) manufactured by DIC Corporation was used.
[0106] Binder resin (B-5): Acrylic resin "Pluscoat" (registered trademark) Z-730 (solid content concentration 25 mass %, solvent: water) manufactured by GOO Chemical Industry Co., Ltd. was used.
[0107] <Reactive Compound (C)> Reactive compounds (C-1): Oxazoline compounds "Epocross" (registered trademark) WS-500 (solid content concentration 40 mass %, solvent: water) manufactured by Nippon Shokubai Co., Ltd. was used.
[0108] ·Reactive compound (C-2): Isocyanate compound (blocked isocyanate) "Elastron" (registered trademark) BN-69 (solid content concentration 40% by mass, water dispersion type) manufactured by Daiichi Kogyo Seiyaku Co., Ltd. was used.
[0109] ·Reactive compound (C-3): Isocyanate compound (blocked isocyanate) "Elastron" (registered trademark) BN-77 (solid content concentration 30% by mass; self-emulsifying type) manufactured by Daiichi Kogyo Seiyaku Co., Ltd. was used.
[0110] Reactive compounds (C-4): Melamine compounds (methylol melamine) "Nicalac" (registered trademark) MW-035 (solid content concentration 70% by mass, solvent: water) manufactured by Sanwa Chemical Co., Ltd. was used.
[0111] Example 1 Resin composition for forming release layer: The release agent (A-1) and the binder resin (B-1) were mixed so that the solid content mass ratio was (A-1) / (B-1)=10 / 90. Then, water was added according to the coating method and the target thickness described below to adjust the solid content concentration, and a resin composition was obtained. Furthermore, in order to improve the coatability to the polyester film, an acetylene-based surfactant ("Olfine" (registered trademark) E1010 manufactured by Nissin Chemical Industry Co., Ltd.) was added so that the amount was 0.1 part by mass per 100 parts by mass of the total mixed resin composition.
[0112] Polyester film: PET pellets (intrinsic viscosity 0.64 dl / g) containing two types of particles (4% by mass of silica particles with a primary particle size of 0.3 μm and 2% by mass of calcium carbonate particles with a primary particle size of 0.8 μm) were thoroughly vacuum dried, fed into an extruder and melted at 280°C, extruded into a sheet from a T-shaped die, and wrapped around a mirror-finished casting drum with a surface temperature of 25°C using an electrostatic casting method and cooled to solidify, thereby obtaining an unstretched film (film A). This unstretched film was heated to 90°C and stretched 3.1 times in the longitudinal direction to obtain a uniaxially stretched film (film B).
[0113] Release film After subjecting the uniaxially stretched film to a corona discharge treatment in air, the resin composition prepared by the method described in the section on resin composition for forming the release layer was applied to a coating thickness of about 6 μm using a wire bar coater. Then, both ends in the width direction of the uniaxially stretched film coated with the resin composition were held by clips and introduced into a tenter, and the solvent of the resin composition was dried in a preheating zone with an atmospheric temperature of 90 to 100 ° C. Then, the film was continuously stretched 3.6 times in the width direction in a stretching zone at 100 ° C., and then heat-treated for 20 seconds in a heat treatment zone at 230 ° C. to form a release layer, and further subjected to a 5% relaxation treatment in the width direction at the same temperature to complete the crystal orientation of the polyester film. Then, the film was cut parallel to the longitudinal direction with a slitter, and both ends in the width direction (uncoated parts) held by the clips were cut and removed, and the release film was wound into a roll. The properties of the obtained release film are shown in Tables 3 and 4.
[0114] (Examples 2 to 17, Comparative Examples 1, 2, and 5) A release film was obtained in the same manner as in Example 1, except that the formulation of the resin composition was changed as shown in Table 2. The properties of the obtained release film are shown in Tables 3 and 4.
[0115] (Examples 18 and 19) A release film was obtained in the same manner as in Example 2, except that PET pellets (Example 18) containing recycled materials in the proportions shown in Table 2 and biomass materials (Example 19) were used as the raw materials for the polyester film. The properties of the obtained release film are shown in Tables 2 and 3. The recycled materials referred to here are shredded uncoated parts removed in the polyester film production process in Examples 1 to 17, and were used by kneading them with virgin materials when producing the polyester film. On the other hand, the biomass raw material used was PET with a biomass content of 15% and in which some of the ethylene glycol units were derived from plants.
[0116] (Example 20) A release film was obtained by the following method using the resin composition of Example 10. A PET film "Lumirror" (registered trademark) T60 (substrate thickness 50 μm) manufactured by Toray Industries, Inc. was used as the polyester resin substrate. The resin composition was applied onto the polyester resin substrate using a wire bar. Next, in order to prevent deformation due to heat, a SUS plate film of the same type as the film was placed and the four sides were held with double clips without any gaps, and then dried and cured in a hot air oven at 230°C for 2 minutes to obtain a release film. The properties of the obtained release film are shown in Tables 3 and 4.
[0117] (Comparative Examples 3 and 4) A release film was obtained in the same manner as in Example 20, except that the formulation of the resin composition and the drying temperature in the hot air oven were as shown in Table 2. The properties of the obtained release film are shown in Tables 3 and 4.
[0118] [Table 2]
[0119] In Example 20 and Comparative Examples 3 and 4, the heat treatment temperature means the drying temperature in a hot air oven.
[0120] [Table 3]
[0121] [Table 4] [Industrial Applicability]
[0122] The release film of the present invention has releasability from adhesives such as acrylic resins and pressure-sensitive adhesives, and stable releasability even after heating, and can be suitably used as a release film for use in the production process of surface protection films, particularly as a release film for use in the production process of surface protection films used for the purpose of preventing scratches on the surfaces of optical components and electronic components during processing, assembly, inspection, transportation, etc.
Claims
1. A release film having a release layer on at least one side of a polyester resin substrate layer, wherein when the surface of the release layer is analyzed by time-of-flight secondary ion mass spectrometry, where K is the peak intensity of a positive ion fragment detected at maximum intensity and P is the peak intensity of a positive ion fragment derived from dimethylsiloxane, P / K is less than 0.01, the surface free energy of the release layer is 25.0 mN / m or less, and the ratio γh / γp of polar strength γp to hydrogen bonding strength γh in the release layer is 1.0 or less.
2. A release film having a release layer on at least one side of a polyester resin substrate layer, and when the surface of the release layer is analyzed by time-of-flight secondary ion mass spectrometry, when the peak intensity of a positive ion fragment detected at the maximum intensity is K and the peak intensity of a positive ion fragment derived from dimethylsiloxane is P, P / K is less than 0.01, and the release layer has a receding contact angle of water, θr, of 85° or more.
3. 2. The release film according to claim 1, wherein the release layer has a receding contact angle θr of water of 85° or more.
4. 4. The release film according to claim 1, wherein R1 is an initial tape peeling force of the release layer, and R2 is a tape peeling force of the release layer after heating at 50° C. for 1 hour. R1 is 4.0 N / 50 mm or less, and R2 / R1 is 5.0 or less.
5. The release film according to claim 1 , comprising at least one of a biomass raw material and a recycled raw material.
6. The release film according to claim 1 , wherein the release layer contains a polyester resin having at least one of a sulfoisophthalic acid (SSIA) group and a carboxyl (COOH) group.
7. 4. The release film according to claim 1, wherein when the surface of the release layer is analyzed by time-of-flight secondary ion mass spectrometry, F / K is less than 0.001, where F is the peak intensity of a fragment of a positive ion derived from methylolmelamine.
8. A laminate comprising the release film according to claim 1 , the release layer being on one surface of the release film, and a pressure-sensitive adhesive layer on the surface of the release layer.
9. 4. A method for producing a release film according to claim 1, comprising the steps of: applying a resin composition for forming a release layer to at least one surface of a polyester resin substrate sheet; stretching the polyester resin substrate sheet after the resin composition has been applied in at least one axial direction; and heating the polyester resin substrate sheet after the stretching to 150° C. or higher to form a release layer, in that order.
Citation Information
Patent Citations
Mold releasing film
JP2004230772A
Release film
JP2004351626A
Process film for producing ceramic green sheet and process for producing the same
JP2010155459A
Pressure-sensitive adhesive composition and surface protection film
JP2012224811A
Laminated film and manufacturing method thereof
JP2015199329A